A Brucella melitensis M5-90 wboA deletion strain is attenuated and enhances vaccine efficacy. Issue 2 (August 2015) - Li, Zhi-Qiang; Shi, Jing-Xue; Fu, Wen-Dong; Zhang, Yu; Zhang, Jing; Wang, Zhen; Li, Tian-Sen; Chen, Chuang-Fu; Guo, Fei; Zhang, Hui
Highlights: The M5-90Δ wboA has low virulence in macrophages and mice. The M5-90Δ wboA can elicit an anti- Brucella -specific IgG response. M5-90Δ wboA immunizations induce a cellular response. M5-90Δ wboA immunizations induces protection against B. melitensis challenge. M5-90Δ wboA could be a potential DIVA vaccine. Abstract: Brucella spp. are Gram-negative intracellular pathogens of both humans and animals that cause great economic burdens in developing countries. Live attenuated vaccines are the most efficient means for the prevention and control of animal Brucellosis. However, Brucella vaccines (strain M5-90 and others) have several drawbacks and do not allow serological differentiation between vaccinated and infected animals. A wboA mutant was derived from Brucella melitensis ( B. melitensis ) vaccine strain M5-90 and tested for virulence and protective efficiency. T-cell responses (CD4 +, CD8 + ), levels of immunoglobulin G (IgG), and cytokine production were observed. WboA was also assessed as a diagnostic marker for Brucellosis. B. melitensis strain M5-90Δ wboA exhibited reduced survival in murine macrophages (RAW 264.7) and BALB/c mice and induced protective immunity in mice comparable to that from the parental strain M5-90. In mice, the wboA mutant elicited an anti- Brucella -specific IgG response and induced the secretion of gamma interferon (IFN-γ) and interleukin-2 (IL-2). In sheep, M5-90Δ wboA immunization induced the secretion of IFN-γ, and serum samples from sheep inoculated with M5-90Δ wboA were negative by Bengal Plate Test (RBPT) and Standard Tube Agglutination Test (STAT). In mice, probes against WboA antigen allowed for serological differentiation between natural infection and vaccination. The M5-90Δ wboA mutant is a potential attenuated live vaccine candidate against virulent B. melitensis 16M infection. It will be further evaluated in livestock.